Long-term trends in ichthyoplankton assemblage structure, biodiversity, and synchrony in the Gulf of Alaska and their relationships to climate. (January 2019) - Marshall, Kristin N.; Duffy-Anderson, Janet T.; Ward, Eric J.; Anderson, Sean C.; Hunsicker, Mary E.; Williams, Benjamin C.
Highlights: Ichthyoplankton surveys reveal changing assemblage structure in the Gulf of Alaska. Species richness increased with increased abundance of warmer water species. Shifts in synchrony coincide with 1988/1989 regime shift. Basin scale drivers appear to have larger influence than local-scale drivers. Ichthyoplankton may be indicators of lower trophic level variability and change. Abstract: Understanding and tracking how ecosystems respond to changing environments is an ongoing challenge. Marine ecosystems in the North Pacific support productive fisheries and diverse ecosystem services, and they are subject to large-scale environmental, human, and ecological perturbations. Ichthyoplankton time-series from these ecosystems may provide an important indicator of lower trophic level dynamics and ecosystem functioning. Here we present a spatiotemporal analysis using data from three decades of ichthyoplankton surveys in the Gulf of Alaska to investigate temporal patterns in indicators of species richness, Shannon diversity, and synchrony. Then we use Dynamic Factor Analysis (DFA) to synthesize the ichthyoplankton assemblage with two dominant trends. We relate the biodiversity indices and DFA trends to local and regional climate indices in the North Pacific. We find evidence for increased temperatures driving increased species richness, and changes in synchrony coincident with shifting assemblage composition and the 1988/1989 regime shift. Shannon diversity was largely driven by the dominance of larval walleye pollock ( Gadus chalcogrammus ). Correlations between climate drivers and DFA trends suggest that the influence of basin scale drivers (North Pacific Gyre Oscillation and the Pacific Decadal Oscillation) were stronger than the influence of local-scale drivers like regional sea surface temperature. Our work demonstrates the potential value of ichthyoplankton surveys to provide indicators of climate-driven ecosystem variability and long-term ecological change.